ANALISIS KESULITAN SISWA MTS KELAS VIII DI BANDUNG BARAT PADA MATERI STATISTIKA - Juliana, Hanapiah Sara; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze the difficulties of grade VIII MTs students in working on math problems with statistical material. The research method used in this research is descriptive method. This research was conducted with the subject of 25 students of MTs Nurul Iman Sindangkerta in the academic year 2019/2020. Data collection techniques in this study were conducting preliminary activities, compiling test questions from instrument questions, consulting test questions, collecting data, analyzing and drawing conclusions. The test questions were given in the form of 5 description questions. The results of the study indicate that the 1st indicator solves a problem to draw conclusions with the criteria for a score of 31% which means very low. The second indicator determines the average or mean value of a given data with a score criterion of 60% which means low. The third indicator analyzes data in the form of a diagram correctly and precisely with a score of 81% which means high. The fourth indicator assesses the truth of the data provided, with a score of 72% which means moderate. And the last indicator 5 makes a solution to a problem with a statistical formula with a score of 69% which means moderate.